INTERNSHIP PROGRAM IN COMPANY:CULTURAL LEARNING PROCESS FOR STUDENTS - Istiadi, Istiadi (Journal of Indonesian Tourism and Policy Studies, 2022)
The internship program is an integral part of the Vocational School Higher Education curriculum. Various knowledge and experiences can be obtained directly as long as students carry out their internships in industries or companies. In a pandemic situation that has recently lasted for approximately two years, the internship program for students within the company is also ongoing even though with different methods and methods, namely what is called WFH (Work From Home). For students, internships are not only an opportunity to learn practical work in the world of work, internships also mean an opportunity to learn about the culture of other people or companies. The internship program is an opportunity for students to learn more about how to adapt to other people's cultures or the existing company culture. With a qualitative approach, this paper tries to explore more deeply how the internship program is a good opportunity for students to be able to know or learn about cultural issues from other people, which include: work culture, time discipline, and other existing habits in a company.